Evaluation of the Strategy for the Implementation of Solar Power Plants in Indonesia Using SWOT Analysis - Nasir, Randy Maulana; Dalimi, Rinaldy (Future Science, 2021)
The demand for electricity in Indonesia is currently growing very massively with an increase in the population of 270 million people, rapid economic growth, as well as the increasing rate of urbanization and large-scale industrialization. Referring to the RUEN, in 2025 renewable energy is projected to increase from 7% to 23%, with the current realization at 11.51% by 2020. In this study, the SWOT method is used to evaluate strategies that have been implemented internally (strengths, weaknesses) and external (opportunities and threats), to achieve the RUEN Target. Based on the results of the study found 5 success factors for the implementation of PV mini-grid, namely economy, environment, marketing, politics, social, and technology. Furthermore, from the SWOT analysis obtained: First, for the social aspect, namely related to population and human resources, each recommended strategy is an aggressive strategy. Second, for the economic aspect, which is related to potential, and the economy, each recommended strategy is an aggressive strategy and a turnaround strategy. Third, for the environmental aspect, the recommended strategy is a diversification strategy. Fourth, for the political aspects, namely regulations and incentives, the recommended strategy is a turnaround strategy. Fifth, for the technological aspect, namely technology, and industrialization, the recommended strategy is aggressive.